Screening and Human Capital Theory: An Empirical Test - Rohling, Thomas (Relations industrielles / Industrial Relations, 1986)
This paper uses the Wiles test in an attempt to distinguish between the Human Capital and Screening theories on the role of higher education. Regressions on Canadian survey data reveal support for Human Capital theory at the expense of Screening theory.